Genetic variability, character association and diversity analyses for economic traits in rice (Oryza sativa L.) - Pratap, N; Singh, PK; Shekhar, R; Soni, SK; Mall, AK (SAARC Journal of Agriculture, 2014)
One hundred high yielding rice genotypes were evaluated to determine character association, variability and diversity for grain yield, yield components and quality characters. High estimates of heritability, genetic advance, genotypic and phenotypic coefficients of variation were recorded for panicle hill-1, flag leaf area and grain yield hill-1. Majority of the traits showed significant and positive associations between yield and yield components like biological yield hill-1 followed by harvest-index as most important traits which need due consideration at the time of devising selection strategy. Thus, presence of several contrasting types of inter-relationships simultaneously would bring improvement in others due to correlated responses. Path analysis might have resulted into cancellation of contrasting associations by each other which ultimately lead to lowering of the net impact. This suggested that selection would be quite efficient in improving yield and yield components in context of germplasm evaluated. The crossing between superior genotypes of above diverse cluster pairs may provide desirable transgressive segregants for developing high yielding varieties of aromatic and non-aromatic rice. Thus, hybridization of Swarna of cluster XI with promising genotypes of cluster VI (Narendra 118, Vandana, Narendra 1, Akashi and Narendra 97) is recommended. DOI: http://dx.doi.org/10.3329/sja.v10i2.18326 SAARC J. Agri., 10(2): 83-94 (2012)